Impact of Digital Technology Use in Improving Productivity and Competitiveness of MSMEs in Medan City - Vincent; Lisa Elianti Nasution (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study aims to determine whether productivity and digital technology have a significant effect on the competitiveness of MSMEs in Medan City. This study uses quantitative data methods and the data source is primary data.The population in this study were MSMEs in Medan city totaling 12,550 MSMEs during 2023. The sample of this study was calculated using the slovin formula so that 99 respondents were obtained and using simple random sampling data collection techniques. Data analysis and testing consists of validity tests, reliability tests, descriptive statistical tests, classical assumption tests, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and determination coefficient tests. The research results indicate that Digital Technology has a significant partial effect on Competitiveness, with a calculated t value of 0.947 > table t value of 0.198. Productivity has a significant partial effect on competitiveness, with a calculated t value of 10.556 > t table of 0.198. Digital technology and competitiveness have a significant simultaneous effect on competitiveness, with a calculated F value of 134.864 > F table of 3.09, and a regression coefficient of 73.8%.